Representation of teacher communication in the live-action film Assassination Classroom - Haadiyan, Mhd. Luthfi; Firmansyah, Firmansyah (FISIP UIN SGD Bandung, 2025)
This study aims to analyze the representation of teacher-student communication in the live-action film Assassination Classroom (2015) using Roland Barthes’ semiotic theory. The research focuses on identifying the denotative, connotative, and mythological meanings constructed through the character of Koro-sensei, who embodies the figure of an ideal teacher. Employing a qualitative method under the constructivist paradigm, the study collects and interprets data from ten key scenes in the film. The findings reveal that Koro-sensei is denotatively portrayed as a non-conventional teacher who engages and empowers marginalized students; connotatively, he represents sacrifice, transformation, and critical engagement with the educational system; mythologically, he reinforces and simultaneously challenges the dominant cultural belief of the teacher as a “hero without reward.” The study concludes that the film blends fantasy and social critique to deliver moral and pedagogical commentary on modern education. The theoretical contribution of this research lies in its advancement of semiotic analysis as a tool for understanding media representations of educators, while its practical relevance highlights the role of film in shaping public perceptions of teaching and educational values. The study encourages further cross-media exploration of teacher myths in global cultural and educational discourse. Contribution: The study bridges theoretical analysis with practical implications, offering a robust model for understanding and critiquing the representation of teachers in contemporary media.